On the roots of Hosoya polynomial. (2nd January 2016) - Shyama, M. P.; Kumar, V. Anil
Abstract: Let G =( V, E ) be a simple and a connected graph of diameter D. The Hosoya polynomial of G. is, where d ( G, k )≥1, is the number of vertex pairs at distance k. The Wiener index of G is the first derivative of the Hosoya polynomial H ( G, x ) at x = 1. In this paper, we study the Hosoya polynomial and Wiener index of some family of graphs. We also discuss the roots of these family of graphs.